Reframing Sustainability Pedagogy in Higher Education: An Integrated Framework Based on Marzano's Dimensions of Learning - Wahjoedi Wahjoedi; Dewi Ariani; Ery Tri Djatmika; Endang Sri Andayani (Universitas Negeri Semarang, 2026)
The integration of the Sustainable Development Goals (SDGs) into higher education has become a central priority within Education for Sustainable Development (ESD), as universities are expected to prepare graduates to address complex sustainability challenges. However, existing sustainability pedagogies remain fragmented and predominantly emphasize technical competencies and problem-solving skills while giving limited attention to the affective, ethical, and metacognitive dimensions required for transformative sustainability learning. This study aims to synthesize contemporary pedagogical approaches for embedding the SDGs in higher education, examine their contribution to transformative sustainability learning, and develop an integrated pedagogical framework based on Marzano's Dimensions of Learning. A Critical Interpretive Synthesis (CIS) reviewed peer-reviewed literature published between 2022 and 2026. Studies indexed in Scopus were purposively selected based on their relevance to sustainability pedagogy, transformative learning, and higher education. The synthesis identified project-based learning, experiential education, and service learning, and transformative pedagogies as the dominant approaches to SDGs integration. These approaches effectively promote systems thinking, interdisciplinary collaboration, and sustainability problem-solving but remain largely competency-oriented, with limited attention to ethical agency, reflective practice, self-system processes, and productive habits of mind. The study concludes that current SDGs pedagogies require a more holistic learning framework. Marzano's Dimensions of Learning offers an integrative scaffold linking cognitive, affective, behavioral, and metacognitive domains to strengthen transformative sustainability learning. The proposed framework provides practical guidance for curriculum redesign, faculty development, assessment reform, and institutional strategies supporting comprehensive SDGs integration in higher education.